The rejoining of double-strand breaks in DNA by human cell extracts. - North, P (1990)
A double-strand DNA break was introduced at a specific site within the lacZ gene of plasmid pUC18 using one of several restriction enzymes, and the plasmid exposed to nuclear extracts from human cell lines. Physical rejoining of DNA was monitored by Southern analysis after gel separation, and the fidelity of rejoining by expression of the lacZ gene after bacterial transformation with the treated plasmid. Breaks at the SalI and EcoRI sites were rejoined by extracts to form circular monomers, but the efficiency of rejoining was much higher at the SalI site. Measurement of rejoining at several adjacent sites having different types of termini, consistently showed a range of efficiencies with 5' 4-base greater than 3' 4-base overhangs and 4-base greater than 2-base greater than no overhang. Similar efficiencies were found for nuclear extracts from transformed cell lines, both from a 'normal' individual and an ataxia-telangiectasia (A-T) patient, and from a non-transformed normal cell culture. In contrast at some sites, especially those with a low rejoin efficiency, the fidelity of rejoining was very much lower for the A-T extracts than for normal cell extracts. Mis-rejoining was, however, unrelated to rejoin efficiency at other sites, suggesting that factors such as the exact sequence at the break site on the molecule may also influence the fidelity of rejoining.